2020
DOI: 10.1136/neurintsurg-2020-016220
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and mechanical thrombectomy in patients with COVID-19: technical observations and patient characteristics

Abstract: BackgroundCOVID-19 infections have been shown to be associated with a range of thromboembolic disease.ObjectiveTo describe our endovascular experience in a consecutive series of patients with COVID-19 who presented with large vessel occlusions, and to describe unique findings in this population.MethodsMechanical thrombectomy was performed on five consecutive patients with COVID-19 with large vessel occlusions. A retrospective study of these patients was performed. Patient demographics, laboratory values, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
131
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 12 publications
7
131
1
5
Order By: Relevance
“…A total sample of 8,771 participants was included in the systematic review. These studies were conducted in many countries worldwide including in China ( 13 , 40 , 43 ), France ( 37 , 39 , 48 , 50 ), India ( 42 ), Iran ( 51 ), Italy ( 32 , 33 , 46 ), the Netherlands ( 34 ), Philippines ( 52 ), Spain ( 44 , 53 ), Turkey ( 58 ), UK ( 41 , 55 ), and the USA ( 21 , 35 , 36 , 45 , 47 , 49 , 54 , 56 , 57 ). Out of 27 studies, eight studies were of retrospective cohort study design, 11 were case series, and nine were case reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total sample of 8,771 participants was included in the systematic review. These studies were conducted in many countries worldwide including in China ( 13 , 40 , 43 ), France ( 37 , 39 , 48 , 50 ), India ( 42 ), Iran ( 51 ), Italy ( 32 , 33 , 46 ), the Netherlands ( 34 ), Philippines ( 52 ), Spain ( 44 , 53 ), Turkey ( 58 ), UK ( 41 , 55 ), and the USA ( 21 , 35 , 36 , 45 , 47 , 49 , 54 , 56 , 57 ). Out of 27 studies, eight studies were of retrospective cohort study design, 11 were case series, and nine were case reports.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of stroke were almost equal for LVO (47 stroke cases in 10 studies) and non-LVO (42 cases in 10 studies). Location of LVOs involved were M1 vessels ( 21 , 37 , 41 , 42 , 44 , 45 , 47 , 53 , 54 ), M2 vessel ( 41 , 42 , 44 , 45 , 47 , 53 ), internal carotid ( 21 , 37 , 42 , 45 , 47 , 53 ), multiteritorial ( 37 , 47 ), posterior cerebral ( 41 , 45 ), basilar ( 37 ), ACA ( 21 , 53 ), and the vertebral artery ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is a report of a COVID 19 patient with AIS secondary due to LVO that underwent successful MT with excellent clinical and angiographic outcome in contrary to majority of reported case prognosis [ 7 ]. Patients with COVID-19 infection, and in particular those requiring ICU care, are more at risk to develop CVD and stroke 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes were noted to be worse in our COVID patients who underwent EVT in a timely manner in comparison with non-COVID patients [18]. These ndings could be related to sequalae of clot fragments and migration of microemboli as described by Wang et al and suggested to be related to the clot composition in COVID-19 patients [15], in addition to the severity of the underlying COVID-19 disease that in conjunction with stroke indicates a worse overall prognosis [6].…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, SARS-CoV-2 pandemic has led to a signi cant decrease in the number of stroke cases presenting to the hospitals, prolonged time from symptoms to hospital arrival and reperfusion [7,8,13]. Furthermore, protocols have been suggested to ensure the safety of stroke team personnel during the pandemic but there is no change in the criteria for mechanical thrombectomy [14,15].…”
Section: Discussionmentioning
confidence: 99%